Shrimp Boom, Migration Boom - Latifah, May (PCD Journal, 2024)
This study examines the expansion of migrant labour as a response to the shrimp boom in Petanahan, Kebumen Regency, which has transformed the local employment structure. The development of shrimp ponds by smallholder farmers, private companies, and the Area-Based Shrimp Ponds Scheme (TUBK) by the Ministry of Marine Affairs and Fisheries (KKP) increased labour demand and triggered migration flows, creating new dynamics in the labour market and potential social-economic tensions. This research employs a qualitative approach, incorporating literature review, in-depth interviews, and field observation. It is supported by Derek Hall and Tania Murray Li's (2011) theory of migrant labour and crop booms to address the research questions and analyse the continuity between booms and migrant labour expansion. The findings of this study reveal three key points: (1) the expansion of shrimp farming in Petanahan has increased labour demand, attracting both local and migrant workers; (2) migrant workers are divided into three categories based on employers: small shrimp farmers, plasma farmers, and TUBK; and (3) the key factors driving migration are more attractive economic incentives compared to the other sectors, limited job opportunities due to low education levels, and the recruitment process conducted by companies.